2015
DOI: 10.3171/2014.12.jns141437
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for arteriovenous malformations after Onyx embolization: a case-control study

Abstract: E mbolization of intracranial arteriovenous malformations (AVMs) was first introduced by Luessenhop and Spence in 1960. 32 Over the next few decades, advances in embolization materials and techniques, including the introduction of transfemoral embolization, detachable or calibrated-leak balloons, particle or liquid embolization, and superselective angiography, made embolization a valuable tool for the management of intracranial AVM. Several reports demonstrated 0%-94% cure rate, 5%-35% morbidity rate, and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…Similarly, several groups have shown a parallel trend of results [37-39]. Sirin, et al [38] in 2006, studied outcomes in 28 patients with gigantic AVM sizes (SM IV-VI), after embo/SRS treatment and obtained obliteration rates as worse as 20%-29% over three years follow-up period.…”
Section: Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, several groups have shown a parallel trend of results [37-39]. Sirin, et al [38] in 2006, studied outcomes in 28 patients with gigantic AVM sizes (SM IV-VI), after embo/SRS treatment and obtained obliteration rates as worse as 20%-29% over three years follow-up period.…”
Section: Reviewmentioning
confidence: 96%
“…Therefore, Dalyai and co-workers concluded that this combined approach is very useful for the treatment of large and complex AVMs [14]. Several investigators have also obtained improved obliteration outcomes with combined treatment, ranging between 50%-78% with minimal SAEs [17,25,37-39], as displayed in Table 4.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…New advances in stereotactic radiosurgical techniques definitely facilitate the application of CyberKnife™ to spinal AVMs [13][14][15]. In this report, we summarize the clinical and radiographic outcomes of five patients with spinal AVM who were treated with CyberKnife™.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al published the first study comparing outcomes between Onyx embolized and non-embolized groups: 25 patients who underwent pre-SRS embolization with matched patients who underwent SRS alone 26. Radiographic obliteration occurred in 6 (24%) embolized patients and in 20 (40%) non-embolized patients.…”
Section: Discussionmentioning
confidence: 99%